Catalytic 1,4-Rhodium(III) Migration Enables 1,3-Enynes to Function as One-Carbon Oxidative Annulation Partners in C–H Functionalizations** - Burns, David J (Angew Chem Int Ed Engl, 2014)
1,3-Enynes containing allylic hydrogens cis to the alkyne are shown to act as one-carbon partners, rather than two-carbon partners, in various rhodium-catalyzed oxidative annulations. The mechanism of these unexpected transformations is proposed to occur through double C–H activation, involving a hitherto rare example of the 1,4-migration of a Rh(III) species. This phenomenon is general across a variety of substrates, and provides a diverse range of heterocyclic products.